Practice patterns and outcomes associated with intravenous albumin in patients with cirrhosis and acute kidney injury - Patidar, Kavish R.; Adibuzzaman, Mohammad; Naved, Mobasshir A.; Rodriquez, Dylan; Slaven, James E.; Grama, Ananth; Desai, Archita P.; Gomez, Eduardo V.; Ghabril, Marwan S.; Nephew, Lauren; Samala, Niharika R.; Anderson, Melissa; et al. (Liver international, 2022)
Background & Aims Guidelines recommend albumin as the plasma‐expander of choice for acute kidney injury (AKI) in cirrhosis. However, the impact of these recommendations on patient outcomes remains unclear. We aimed to determine the practice‐patterns and outcomes associated with albumin use in a large, nationwide‐US cohort of hospitalized cirrhotics with AKI. Methods A retrospective cohort study was performed in hospitalized cirrhotics with AKI using Cerner‐Health‐Facts database from January 2009 to March 2018. 6786 were included for analysis on albumin‐practice‐patterns, and 4126 had available outcomes data. Propensity‐score‐adjusted model was used to determine the association between albumin use, AKI‐recovery and in‐hospital survival. Results Median age was 61‐years (60% male, 70% white), median serum‐creatinine was 1.8 mg/dL and median Model for End‐stage Liver Disease Sodium (MELD‐Na) score was 24. Albumin was given to 35% of patients, of which 50% received albumin within 48‐hours of AKI‐onset, and 17% received appropriate weight‐based dosing. Albumin was used more frequently in patients with advanced complications of cirrhosis, higher MELD‐Na scores and patients admitted to urban‐teaching hospitals. After propensity‐matching and multivariable adjustment, albumin use was not associated with AKI‐recovery (odds ratio [OR] 0.70, 95% confidence‐interval [CI]: 0.59‐1.07, P = .130) or in‐hospital survival (OR 0.76 [95% CI: 0.46‐1.25], P = .280), compared with crystalloids. Findings were unchanged in subgroup analyses of patients with varying cirrhosis complications and disease severity. Conclusions USA hospitalized patients with cirrhosis and AKI frequently do not receive intravenous albumin, and albumin use was not associated with improved clinical outcomes. Prospective randomised trials are direly needed to evaluate the impact of albumin in cirrhotics with AKI.